(untitled) (International Seven Journal of Multidisciplinary, 2024)
This paper presents the importance of a geological-geotechnical survey in order to support the construction of a building in the Samambaia Administrative Region, Federal District, Brazil. The study was carried out in stages. Firstly, a geological-geotechnical study was carried out for the area where the project would be located, based on pre-existing analyses and studies. Next, the analyses carried out in the project area, together with the field investigations (SPT and rotary drilling), added to the topographic survey, helped to define the type of foundation and containment adopted, as well as a greater degree of accuracy of the subsoil material in the excavation area. For the area studied, there was considerable variability in the soils, with a predominance of sand, clayey sand and sandy clay. In addition, there was a considerable presence of rhythmites with quartzites and clayey, silty and sandy laminar intercalations. These surveys and studies were of the utmost importance when it came to choosing the right executive process and making the necessary adjustments during excavations.